Quantitation and clinical evaluation of plasma aldosterone by ultra-performance liquid chromatography–mass spectrometry - Tan, Xin; Li, Fengjuan; Wang, Xue; Wang, Yuan (Journal of Chromatography A, 2020)
•Reference intervals of aldosterone for healthy volunteers were established.•Aldosterone levels in 888 hypertensive patients were measured.•We prepared samples with 90 µL plasma and measured aldosterone using UPLC–MS/MS.•Our UPLC–MS/MS method had higher sensitivity and wider linear range. Accurate quantitation of aldosterone is critical for the clinical detection of hypertension. However, no reference intervals for aldosterone in healthy volunteers and patients with hypertension have yet been established using highly sensitive methods with a wide linear range based on low plasma volumes. We developed a modified ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) method for the quantitation of aldosterone and established reference intervals for healthy volunteers and patients with hypertension. We measured aldosterone by UPLC–MS/MS in human plasma samples (90 µL). We established a reference range for aldosterone based on blood collected midmorning from 888 patients with hypertension and 258 seated, normotensive subjects. The linear range was 10–5000 pg/mL (r2 > 0.995), with a limit of quantification of 10 pg/mL. Similar results were obtained using different collection tubes, including EDTA plasma, sodium citrate plasma, and serum, respectively. Based on a comparison of results from UPLC–MS/MS and enzyme-linked immunosorbent assay, we derived the equation: UPLC–MS/MS = 0.8444 × ELISA + 1.162. Aldosterone concentrations in normotensive subjects ranged from 12.76 to 196.21 pg/mL, with no effect of age or sex on the reference interval. Aldosterone levels were significantly higher in patients with hypertension versus healthy controls (median: 71.05 versus 52.54 pg/mL, P < 0.0001), and patients with secondary hypertension versus primary hypertension (median: 67.25 versus 46.70 pg/mL, P = 0.0128) which were age- and sex-matched. Reference intervals for aldosterone in healthy individuals and patients with hypertension were established based on an improved UPLC–MS/MS method with higher sensitivity, a wider linear range, and lower plasma volume.